2003
DOI: 10.1073/pnas.1834348100
|View full text |Cite
|
Sign up to set email alerts
|

Pyk2 regulates multiple signaling events crucial for macrophage morphology and migration

Abstract: The biological role of the protein tyrosine kinase, Pyk2, was explored by targeting the Pyk2 gene by homologous recombination. Pyk2؊͞؊ mice are viable and fertile, without overt impairment in development or behavior. However, the morphology and behavior of Pyk2؊͞؊ macrophages were impaired. Macrophages isolated from mutant mice failed to become polarized, to undergo membrane ruffling, and to migrate in response to chemokine stimulation. Moreover, the contractile activity in the lamellipodia of Pyk2؊͞؊ macropha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
289
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 271 publications
(308 citation statements)
references
References 40 publications
16
289
1
Order By: Relevance
“…Pyk2 is enriched in adult neurons and plays an important role in neuronal plasticity [2][3][4][5][6]. In non-neuronal cells, Pyk2 is involved in osteoclast function [7], macrophage migration [8], and focal adhesion disassembly [9]. Neuronal Pyk2 is 5 kDa larger than in cells from the hematopoietic lineage, due to the retention of an additional exon coding for a peptide between the kinase and focal adhesion targeting (FAT) domains [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Pyk2 is enriched in adult neurons and plays an important role in neuronal plasticity [2][3][4][5][6]. In non-neuronal cells, Pyk2 is involved in osteoclast function [7], macrophage migration [8], and focal adhesion disassembly [9]. Neuronal Pyk2 is 5 kDa larger than in cells from the hematopoietic lineage, due to the retention of an additional exon coding for a peptide between the kinase and focal adhesion targeting (FAT) domains [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Pyk2 knock-out mice are viable and fertile (49), whereas knocking out FAK results in embryonic lethality (50), suggesting the selective inhibition of Pyk2 may have therapeutic advantages. In this regard it is notable that recently inhibitors with strong selectivity for Pyk2 over FAK have been identified (51).…”
Section: Discussionmentioning
confidence: 99%
“…PYK2 (proline-rich tyrosine kinase 2, also known as RAFTK, CADTK or CAKb), the second member of the focal adhesion kinase family, regulates focal adhesion turnover (Avraham et al, 2000;Gelman, 2003) and cell motility (Sieg et al, 1998;Guinamard et al, 2000;Ivankovic-Dikic et al, 2000;Okigaki et al, 2003); therefore, we studied the role of PYK2 in cell-cell repulsion. We found that PYK2 localizes at focal adhesions and promotes cell-cell repulsion.…”
Section: Introductionmentioning
confidence: 99%